2023
DOI: 10.3390/su15054301
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Donors Donate? A Study on Donation-Based Crowdfunding in Malaysia

Abstract: This study employed the Stimulus–Organism–Response (S-O-R) framework to investigate how social support and quality of the community affect the purpose to donate through donation-based crowdfunding. The online poll generated 359 responses, and the data were statistically analysed using the partial least square structural equation modelling (PLS-SEM) approach. Path coefficient analysis is also applied to figure out the outcomes of the relationships between the components. The results showed that service and syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…The SOR model has been extensively applied and proved effective in understanding consumer perceptions and behavioral responses toward sustainable fashion or general fashion such as willingness to buy slow fashion products [12], environmentally friendly apparel purchase intention [21], second-hand fashion consumption [22,23], used apparel donation behavior [24], and adoption of omnichannel fashion retailing [19]. The successful applications of the SOR model in prior studies have proved its versatility and applicability in the present research.…”
Section: Stimulus-organism-response (Sor) Modelmentioning
confidence: 75%
“…The SOR model has been extensively applied and proved effective in understanding consumer perceptions and behavioral responses toward sustainable fashion or general fashion such as willingness to buy slow fashion products [12], environmentally friendly apparel purchase intention [21], second-hand fashion consumption [22,23], used apparel donation behavior [24], and adoption of omnichannel fashion retailing [19]. The successful applications of the SOR model in prior studies have proved its versatility and applicability in the present research.…”
Section: Stimulus-organism-response (Sor) Modelmentioning
confidence: 75%
“…Over the decades, the S-O-R (Stimulus-Organism-Response) framework has been utilized as a guide for academic re-search to understand consumer behaviors related to sustainable fashion consumption. This includes areas such as fashion rental services [20], environmentally friendly apparel [21], and used apparel donation behavior [22]. Due to its comprehensive approach to capturing the relationship between environmental stimuli, internal psychological processes, and consumer behavior, the S-O-R framework was adopted by this research to examine second-hand clothing consumption.…”
Section: Stimulus-organism-response (Sor) Modelmentioning
confidence: 99%
“…Contributors are more likely to donate when they have confidence in the campaign organisers and believe that their donations will be used for specific purposes. Kamarudin et al (2023) conducted a study that revealed that trust has a positive impact on the outcomes of social crowdfunding campaigns in Malaysia. Supported by other studies, Cordova et al (2015) argue that campaigns characterised by higher levels of trust were more likely to successfully achieve their funding goals and receive positive feedback from contributors.…”
Section: Trustmentioning
confidence: 99%